Essays on the Impact of Foreign Direct Investments in Africa - (:unkn) unknown (My University, 2016)
The objective of this thesis is to analyze the impact of foreign direct investment (FDI) inflows towards Africa on economic growth, industrialization, and technological transfer. Analyses aiming at studying the nexuses FDI-economic growth and FDI-industrialization are based on macroeconomic data from respectively 50 and 49 African countries observed during the period from 1980 to 2009; and analyses on FDI related technological spillovers are based on Kenyan firm-level data observed in the manufacturing sector during the period 2012/2013. Concerning the FDI-economic growth nexus, it is found that FDI inflows had a significant impact on economic growth in the African region during the period of interest. It also finds that while the low level of human resources did not limit the impact of FDI, and that the impact of FDI on economic growth was negative or non-significant during the period from 1980 to 1994 and positive during the period from 1995 to 2009. The results indicate that FDI most likely did not have a significant impact on the industrialization of African countries. Concerning the existence of FDI-related technological transfer, it is found that FDI inflows did not spur innovation in local firms competing against multinational firms.
Keywords: African Research